La responsabilidad penal de los adolescentes infractores en el código orgánico de la niñez y adolescencia - Veintimilla Figueroa, Yhasmin (2017)
The current investigative work is directed to "The criminal responsibility of juvenile offenders in the Organic Code of Children and Adolescents", which analyzes the criminal responsibility of juvenile offenders, be subject to the norms indicated in the Organic Code of the Childhood and Adolescence, which allows the application of socio-educational measures, which are protectionist of adolescents, but harmful to society, when verifying the increase of crime in our country. It must reform the Code on children and adolescents by determining that it is considered a punishable offense for the wrongful acts committed, with penalties greater than ten years as established in the Comprehensive Criminal Code, for the reason that the law allows them to exercise The optional vote, according to the Constitution the adolescents in case of divorce choose with which parent they want to go live and in case of transit they grant them driving license, that is to say they are considered as capable people with power of discernment, for They must also be held criminally responsible for crimes committed. In this thesis, I demonstrate that the sanctions imposed on juvenile offenders are based on socio-educational measures that are administered by a Judge of the Childhood and Adolescence, in accordance with the regulations established in the Code of Children and Adolescents; Such as: reprimand, reprimand and imposition of rules of conduct, family counseling and support, reparation of the damage caused, community services, assisted freedom, home detention, weekend internment, internment of semi-liberty, institutional internment; Which means that adolescents who commit offenses after having committed a serious crime, with the application of socio-educational measures, continue in the regularity of criminal acts, and do not achieve a social rehabilitation of the offending adolescent, they are also protected and guaranteed their rights Situation that is taken advantage of to continue in criminal acts for being considered subjects inimputable. It is therefore imperative to reform the Code on Children and Adolescents; On the incomputability of the juvenile offenders, thus guaranteeing citizen security. In the theoretical and field work of the present thesis I was able to obtain criteria with clear and precise foundations, the same ones that helped me to verify objectives and contrast hypotheses, allowing me to strengthen the proposed